2020
DOI: 10.1186/s13011-020-00259-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perfectionism and attitudes toward doping in young athletes: the mediating role of autonomous and controlled motivation

Abstract: Background: Recent studies suggest that autonomous and controlled motivation may mediate the relationship between perfectionism and attitudes toward doping. The purpose of this study was to investigate the association among perfectionistic strivings, perfectionistic concerns, autonomous motivation, controlled motivation, and attitudes toward doping in young athletes. The potential mediating role of autonomous and controlled motivation was examined. Methods: Two hundred and forty-three Chinese athletes were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…A complete overview over the bias check is presented in Supplementary material 1: Table H. Only three studies were identified for selective reporting (Candela et al, 2014;Desalegn et al, 2016;Soltanabadi et al, 2015), just like only seven studies indicated high risk for correlation biases (Campian et al, 2018;Kavussanu et al, 2016;Mudrak et al, 2018;Nicholls et al, 2019b;Ogama et al, 2019;Sukys &Karanauskiene, 2020 andWang et al, 2020). High risk for socially desired responding style was identified in the vast majority of the studies.…”
Section: Bias Assessment Within Studiesmentioning
confidence: 99%
“…A complete overview over the bias check is presented in Supplementary material 1: Table H. Only three studies were identified for selective reporting (Candela et al, 2014;Desalegn et al, 2016;Soltanabadi et al, 2015), just like only seven studies indicated high risk for correlation biases (Campian et al, 2018;Kavussanu et al, 2016;Mudrak et al, 2018;Nicholls et al, 2019b;Ogama et al, 2019;Sukys &Karanauskiene, 2020 andWang et al, 2020). High risk for socially desired responding style was identified in the vast majority of the studies.…”
Section: Bias Assessment Within Studiesmentioning
confidence: 99%
“…However, to be correctly interpreted -and fought -doping must also be seen as a cultural and educational problem (Isidori, 2017) and is studied as an ethical problem that has medical and legal riots Barkoukis et al, 2019). Therefore, in order to defeat this disease of sport in addition to the controls ordered by the various sports authorities and sanctions an educational approach is necessary as a preventive measure (Wang, et al, 2020). Indeed, Doping is closely linked to a lack of "educational agents" such as family school religious associations federations and sports clubs (Goldberg,2005;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to defeat this disease of sport in addition to the controls ordered by the various sports authorities and sanctions an educational approach is necessary as a preventive measure (Wang, et al, 2020). Indeed, Doping is closely linked to a lack of "educational agents" such as family school religious associations federations and sports clubs (Goldberg,2005;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different evaluated items in athletes, lower self-esteem and higher anxiety are two related factors for doping in adolescent athletes. However higher self-esteem and lower anxiety levels are seen in older athletes [6]. Mudrak et al also reported lower self-esteem and higher anxiety level among athletes performing doping and these disorders were also interrelated with high-risk behaviors including cannabis and alcohol abuse.…”
Section: Introductionmentioning
confidence: 96%